An Innovation Design Approach for Product Service Systems Based on TRIZ and Function Incentive - Jie Jiang; Yan Li; Lidan Li; Changchun Zhou; Yuxiang Huo; Qian Li (Complexity)
Good balance between product and service is the key in the innovative design of product service systems (PSS). In this study, the evolution route of the PSS based on Teoriya Resheniya Izobretatelskikh Zadatch ideal final result was provided. The function model of the PSS was constructed according to the service blueprint and function system diagrams. On this basis, an innovation design method of the PSS based on function incentive was established. The function incentive strategies included function synergy, function supplement, and function substitution. Finally, the PSS design process of agricultural machinery based on computer-aided innovation platform was analyzed to verify this method.